Scottish education in the twentieth century - Paterson, Lindsay (Edinburgh University Press, 2003)
Scotland's education system has been claimed by many to be one of the most successful in the world and its alleged decline in recent decades has generated a great deal of controversy. This book is the first full history of twentieth-century Scottish education.